Etiopathogenesis and surgical treatment of epithelial pilonidal sinus - A. Yu. Titov; I. V. Kostarev; A. K. Batischev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present modern approaches to surgical management of chronic inflammation of epithelial pilonidal sinus (EPS), efficacy of treatment methods, rates of complications and relapses.Summary. Up to now there is no common judgement on etiology and pathogenesis of epithelial pilonidal sinus. All theories may be divided to two basic classes: congenital and acquired EPS. In the Russia opinions on development of this disease cardinally differ from that of foreign scientists. Traditionally in Russian domestic literature EPS is considered as congenital anomaly, while foreign researchers decline acquired etiology of this disease. Furthermore issues of optimal surgical treatment choice are solved. The long period of wound healing, postoperative pain and quite frequent disease relapses remain common in such patients. According to various authors, EPS relapse rate makes 20 to 40% irrespective of treatment method. Attempts to find the radical EPS treatment method providing the lowest pain level, small wound surface and allowing the lowest possible disability period and motor activity limitation, stimulate development of new surgical treatment methods and improvement of already established operations.Conclusion. Now methods of EPS surgical treatment should meet following requirements: be simple in performance, provide low pain, rapid restoration of work capacity and social activity. Application of modern surgical approaches strictly following indications and individual approach to choice of surgery provides maximal conformity to the specified requirements.